LIVELIHOOD SUPPORT OF JOINT FOREST MANAGEMENT (JFM) IN RURAL INDIA - NASEER A. MIR; RAZA ALI ABIDI; HILAL AHMAD BHAT; MALIK ASIF (International Journal of Pharma and Bio Sciences, 2014)
The total forest cover of the country is believed to be 69.09 million hectares which constitutes about 21.02 % of the total geographical area of the country. The report further claims that there has been an increase of 3.13 Mha of forest cover in the country since 1997, i.e., from 65.96 Mha to 69.09 Mha at present. There are at least 200,000 villages that live inside or on the fringes of forest and an estimated 275 million people significantly depend on forests for their sustenance and livelihood. As per 1990 JFM guidelines from the Centre, all the states have resolved to implement JFM making it one of the largest community based natural resource management programme in the world. The idea is to bring 33% of the forest cover in India within this joint forest programme by the year 2020. By the end of 2006, close to 100,000 communities have participated/adopted one or the other form of JFM covering an area of about 22 million hectares in 28 states. The Joint Forest Management program in India is one of the largest co-management efforts in natural resource conservation in the world apart from providing livelihoods to forest dependent populations. Joint forest management provides crucial subsistence needs of housing materials, food, medicine, fuel-wood, small timber and non timber forest products. It is also argued that the rural population in forest fringe areas is reliant on forest resources for their livelihoods as well as a way of life both socially and culturally. In every case, joint forests management offer vast potential for poverty alleviation among the forest-dependent poor. The importance of forest resources among fringe communities for sustenance has become substantial. The evolving concept of community forest management has naturally brought to the fore various interrelated issues concerning forest management.